A SYSTEMATIC REVIEW AND META-ANALYSIS: RISK FACTORS OF MORTALITY COVID-19: Sistematik Review dan Meta-Analisis: Faktor Risiko Kematian COVID-19 - Febrianti, Thresya; Falmuriat, Qurratu (Universitas Airlangga, 2024)
Background: COVID-19 is still a threat throughout the world because of its high morbidity and mortality. Comorbid diseases like hypertension, diabetes mellitus, and heart disease are some of the factors in the high severity and mortality of COVID-19 patients. Purpose: The study aims to analyze the effect of risk factors on COVID-19 mortality using a systematic review and meta-analysis. Methods: Articles were taken from online journal portals Pubmed, Garuda, and Google Cendekia, and all were published from October 2019 to December 2021 in full text and with an observational study design. The keywords used in searching the articles were